Current Blood Clotting Schemes - Quick, A. J; Professor Emeritus of Biochemistry (Thrombosis and Haemostasis, 1966)
Currently, there are three schemes to explain the coagulation of blood, each representing an attempt to unravel the complex process. The lack of agreement can be attributed, first, to the experimental approaches and, secondly, to the objective. To evaluate accurately the reliability of the various methods employed in isolating clotting factors and in studying their properties would require the wisdom of Solomon. While both the cascade sequence theory and Seegers’ approach have as their main aim to study the chemistry of blood coagulation, the primary objective of the expanded classical theory is to serve diagnostically. The final goal - the correlation of blood coagulation and hemostasis - can only come clinically. The more clearly the chemistry of the coagulation mechanism is understood and the more accurate the diagnosis, the better will be the prospect of approaching successfully the problem of hemostasis.